The wettability and surface free energy of sawn, sliced and sanded european oak wood - Agnieszka Jankowska (Maderas: Ciencia y Tecnología, 2018)
The main objective of this work was to evaluate the effects of two machining processes on European oak wood surface characteristics. The relationships between wettability, free surface energy and machining methods were studied. Sawing and slicing, with or without sanding, were used to prepare surfaces prior to testing whether they produce surfaces with different characteristics. For the wood surfaces machined by slicing and sawing, there was a significant difference in contact angle measurements. This indicates that the influence of machining processes such as slicing and sawing on contact angle value is remarkable. Sanded surfaces showed good wettability and high process roughness.